A phase‐variable absorption feature in the X‐ray spectrum of the magnetar SGR 0418+57291. (March 2014) - Tiengo, A.; Esposito, P.; Mereghetti, S.; Turolla, R.; Nobii, L.; Gastaldello, F.; Götz, D.; Israel, G.L.; Rea, N.; Stella, L.; Zane, S.; Bignami, G.F.
Abstract An absorption feature, the properties of which strongly depend on the pulse phase, has been recently discovered in the X‐ray spectrum of the soft gamma repeater SGR0418+5729. If interpreted as a proton cyclotron line, its energy implies a magnetic field ranging from 2× 1014 G to more than 1015 G, which confirms the magnetar interpretation for this source and provides us with the most direct measurement of the magnetic field intensity of an isolated neutron star. The lower value of the dipole field inferred from the timing parameters for SGR 0418+5729 (B = 6× 1012 G) requires that the high magnetic field responsible for the observed feature resides in a strong multi‐polar component located close to the neutron star surface, in agreement with the predictions of the magnetar model. (© 2014 WILEY‐VCH Verlag GmbH & Co. KGaA, Weinheim)